MOLECULAR CHARACTERIZATION AND EPIDEMIOLOGY OF DENGUE VIRUS IN CENTRAL INDIA: INSIGHTS INTO SEROTYPE DISTRIBUTION AND EVOLUTIONARY TRENDS - Rashmi Ranjan Rout; Dr. Debasish Samal; Dr. Monalisa Subudhi; Dr. V.K. Ramnani (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Dengue virus (DENV) is a significant public health concern, particularly in tropical and subtropical regions where it causes a wide range of clinical manifestations, from mild febrile illness to severe forms like dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS). This study focuses on the molecular characterization of DENV strains circulating in Central India, an area prone to frequent dengue outbreaks. By analyzing genomic data from clinical samples, we aimed to elucidate the serotype distribution, genetic diversity, and evolutionary patterns of DENV in this region. The study also explores the epidemiological implications of these molecular characteristics, providing valuable insights into local transmission dynamics and public health challenges. The findings highlight the critical role of continuous molecular surveillance in informing effective dengue control strategies.